Genomic evidence of genetic diversity and functional evolution in Flavobacterium columnare - Han, Rui; Hong, Yuhao; Xu, Ruilong; Guo, Wenjie; Zhang, Mingshu; Lu, Zijun; Han, Qing; Mo, Zequan; Dan, Xueming; Li, Yanwei (Frontiers in Microbiology, 2023)
Flavobacterium columnare is the causative agent of columnaris disease in freshwater fish. Columnaris disease can cause heavy economic losses in aquaculture.Herein, whole genome sequencing was used to characterize this pathogen. F. columnare isolate AH-01 had a circular chromosome and plasmid, which encoded a total of 3022 genes. Isolate GX-01 only had a circular chromosome and encoded 2965 genes. Genomic islands, prophage regions, and CRISPR/Cas systems were identified in both genomes. Both genomes presented evidence of gene variation and horizontal transfer, the essential components of genetic diversity, genome plasticity, and functional evolution. Single-gene phylogeny and comparative genome analyses were performed to investigate the variation and evolution of this pathogen. Genetic analysis of 16S rRNA and housekeeping gene sequences significantly clustered 55 F. columnare isolates into four clades. The intragroup identity of the 16s rRNA gene exceeded 99%, while the intergroup identity was below the species delineation threshold. We discovered significant translocation, inversion, and rearrangement events that influenced local synteny within each group. Notably, the observed alignments varied considerably among all the groups studied. The core genomes of all strains with available sequences comprised 747 genes, corresponding to approximately 25% of the genome. Core genome multilocus sequence typing, genome-wide orthology and phylogenetic analyses, and average nucleotide identity suggested the currently existing F. columnare was an assemblage of several distinct species, with levels of divergence at least equivalent to those between recognized bacterial species. The present investigation provided genomic evidence of gene variation and horizontal transfer, which was the basis of genetic diversity, genome plasticity, and functional evolution.The findings supported a proposed new taxonomic perspective of F. columnare.